Gender and Peer Effects in Social Networks - Julie Beugnot; Bernard Fortin; Guy Lacroix; Marie Claire Villeval (Institute of Labor Economics (IZA), 2017)
We investigate whether peer effects at work differ by gender and whether the gender difference in peer effects if any depends on work organization, precisely the structure of social networks. We develop a social network model with gender heterogeneity that we test by means of a real-effort laboratory experiment. We compare sequential networks in which information on peers flows exclusively downward (from peers to the worker) and simultaneous networks where it disseminates bi-directionally along an undirected line (from peers to the worker and from the worker to peers). We identify strong gender differences in peer effects, as males' effort increases with peers' performance in both types of network, whereas females behave conditionally. While they are influenced by peers in sequential networks, females disregard their peers' performance when information flows in both directions. We reject that the difference between networks is driven by having one's performance observed by others or by the presence of peers in the same session in simultaneous networks. We interpret the gender difference in terms of perception of a higher competitiveness of the environment in simultaneous than in sequential networks because of the bi-directional flow of information.
Keywords: C91; J16; J24; J31; M52; 330; gender; peer effects; social networks; work effort; experiment